2016
DOI: 10.1111/den.12706
|View full text |Cite
|
Sign up to set email alerts
|

Specific locations of linear furrows in patients with esophageal eosinophilia

Abstract: Investigation of these endoscopic characteristics, especially by focusing on linear furrows in esophageal mucosal fold valleys, may provide important clues for more accurate diagnosis of EoE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…For the diagnosis and monitoring of the activities of EoE and EGE, an endoscopic investigation and histological assessment of biopsy specimens are considered to be required ( 1 , 10 , 11 ). However, endoscopic abnormalities are often non-specific and difficult to identify ( 12 - 14 ). Furthermore, histological findings for grading eosinophil infiltration are not always accurate because of the uneven patchy distribution of eosinophils in the esophago-gastro-intestinal mucosa ( 1 , 10 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the diagnosis and monitoring of the activities of EoE and EGE, an endoscopic investigation and histological assessment of biopsy specimens are considered to be required ( 1 , 10 , 11 ). However, endoscopic abnormalities are often non-specific and difficult to identify ( 12 - 14 ). Furthermore, histological findings for grading eosinophil infiltration are not always accurate because of the uneven patchy distribution of eosinophils in the esophago-gastro-intestinal mucosa ( 1 , 10 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, endoscopic abnormalities are often non-specific and difficult to identify ( 12 - 14 ). Furthermore, histological findings for grading eosinophil infiltration are not always accurate because of the uneven patchy distribution of eosinophils in the esophago-gastro-intestinal mucosa ( 1 , 10 , 14 ). In addition, an endoscopic examination is invasive, and repeated examinations for activity evaluations are difficult to perform.…”
Section: Introductionmentioning
confidence: 99%
“…The position of ABS in relation to esophageal longitudinal folds was also assessed. We recently reported that linear furrows were found to be located in mucosal fold valleys in all affected patients 18 . Interestingly, in all of the present patients with ABS, that was found in esophageal longitudinal mucosal fold ridges, where it did not appear in the valleys.…”
Section: Resultsmentioning
confidence: 91%
“…As mentioned above, the importance of random biopsies has been highlighted, irrespective of endoscopic findings since some EoE patients present with apparently normal mucosa via endoscopy [80]. However, the degree of EE is more intense in the areas containing white exudates [34,105], in linear furrows [32,106], or in the lower esophagus compared with the proximal region [34,104], suggesting that the histological detection of EE may also be influenced by the site of the biopsies in addition to the number of biopsy samples obtained. When the peak of infiltrating eosinophils is \14 eosinophils/HPF in patients suspected of EoE, re-biopsies can aid in the definitive diagnosis of EoE [107].…”
Section: Histological Findingsmentioning
confidence: 99%